Military as a National Unity Pillar of Pakistan: Issues and Challenges - Ramisha (Pakistan Languages and Humanities Review, 2024)
This study explores Pakistan's military's dual function as a source of sociopolitical conflict and a unifying force, as well as its effects on socioeconomic development, governance, and national unity. The military has been essential in preserving territorial integrity, guaranteeing stability and tackling issues related to regional security since 1947. But its power in politics has frequently hampered the growth of democracy, widened regional and ethnic divides, and strained links between the military and the civilian population. To assess the military's contributions and difficulties in promoting national cohesiveness, this study uses a qualitative technique that includes case studies, historical analysis, and a critical examination of the body of current literature. The results show that although the military's role in internal security and counterterrorism has been essential to stability, it has also sparked worries about human rights abuses and civilian casualties. Additionally, political polarization has been sustained and the development of democratic institutions has been postponed due to the military's dominance in civilian rule. In order to reframe the military's role in fostering unity, the report emphasizes the necessity of changes, such as improved civilian control, democratic consolidation, and equal socioeconomic development. In order to match the military's contributions with Pakistan's objectives of equitable growth and democratic governance, these structural issues must be resolved.